Quantitative proteomic and metabolomic analysis of Dictyophora indusiata fruiting bodies during post-harvest morphological development. (1st March 2021) - Wang, Jinqiu; Wen, Xuefei; Zhang, Yayu; Zou, Pingping; Cheng, Lei; Gan, Renyou; Li, Xiang; Liu, Dayu; Geng, Fang
Graphical abstract: Highlights: Quantitative metabolomic and proteomic analysis of D. indusiata were performed. A total of 951 DEPs and 338 DAMs were identified. Upregulated catabolism provides materials for the maturity of D. indusiata. Enhanced energy metabolism provides momentum for the morphological development. Oxidative stress response of the mature fruiting body was upregulated. Abstract: The differences in Dictyophora indusiata fruiting bodies between peach-shaped and mature stage during the postharvest were systematically investigated through quantitative proteomic and metabolomic analyses. A total of 951 differentially expressed proteins were identified, 571 upregulated and 380 downregulated in the mature fruiting body; additionally, 173 upregulated and 165 downregulated differential abundance metabolites were screened. Integrated proteome and metabolome analyses showed that, during the maturation of D. indusiata fruiting bodies, glycerophospholipids were hydrolyzed and drastically decreased, the degradation of glucan was upregulated, the degradation and synthesis of chitin were simultaneously enhanced, and proteins were dominated via catabolism. Along with vigorous material metabolism, energy production was enhanced through the upregulated TCA-cycles and oxidative phosphorylation. In addition, the synthesis of antioxidant substances and the decomposition of peroxides were enhanced in mature fruiting bodies. These omics analyses of D. indusiata provide high-throughput data and reveal the changes in the post-harvest morphological development.